Peningkatan Kedisiplinan, Motivasi, Kompetensi, Pelatihan Manajemen Keuangan, Literasi Perencanaan Keuangan dan Perlindungan Guru dalam Pembentukan Budaya Organisasi di Yayasan Mutakabbir Kabupaten Bogor - Muhammad Rizal Saragih; Rusdi Rusdi; Dinar Ambarita; Prima Sadewa; Mawardi Nurullah; Julian Muhammad Hasan; Liana Dwi Septiningrum; Eka Rima Prasetya; Moh. Yuddy Yudawirawan; Dewi Ulfah Arini; Sujarwo Sujarwo; Muslim Muslim; Fery Citra Febriyanto; Eko Sasongko Priyadi; Diantia Amendy (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Organizational culture within educational institutions plays a vital role in shaping the behavior, professionalism, and performance of educators and students alike. Yayasan Mutakabbir in Bogor Regency has identified key challenges related to discipline, motivation, competency, financial management, and the protection of teachers as part of its organizational development. To address these issues, a Community Service Program (PKM) titled